Wspieranie rozwoju kreatywności dziecka jako element praktyki logopedycznej. O możliwych związkach logopedii z pedagogiką twórczości - Galewska-Kustra, Marta (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Logopedics and pedagogy of creativity are the disciplines whose areas of research interests are different. Some may say that they have nothing in common. The main tasks and goals undertaken by the speech therapists are different from those by creativity educators. Speech therapists’ work is directly connected with prevention and therapy of speech disorders. Creativity educator supports, enhances and develops creative abilities, creative attitude of children, adolescents and adults. However, the goals of creativity education may become a part of the speech therapy practice. This article is an attempt to illustrate the possible relations between pedagogy of creativity and logopedics, and to show the practical ways in which the practice of speech therapy may become an opportunity to develop children’s creativity.